ChemInform Abstract: A Facile Preparation of Various N‐Heterocycles Using Amides and Olefins. Issue 24 (2nd June 2014) - Gratia, Synthia S.; Vigneau, Edward S.; Eltayeb, Sumiea; Patel, Kishan; Meyerhoefer, Terence J.; Kershaw, Sonia; Huang, Victor; De Castro, Michael
Abstract A convenient synthesis of a variety of N‐heterocycles including oxazolines, thiazolines, and dihydrodoxazines is accomplished by NIS‐promoted addition of amides or heteroanalogues amides to olefins.